Яичко: [потешная сказка] / А. Елисеев ; ил. автора - Елисеев Анатолий (ЭНАС-КНИГА, 2012)
Для дошкольников. Экземпляры: ФО-1/1,4/2,8/3,15/4,ДО/5 (20130424) / Инвентарный номер: 1 / Цена: 198.00 / Авт.знак: Е 51 / ББК: 84(2Рос)